2008
DOI: 10.1149/1.2976305
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Dependence of Proton Conductivity of Amorphous Aluminosilicate Nanofilm

Abstract: Al x Si 1−x O n films exhibit a drastic change of proton conductivity across the film by reducing their thickness to less than 100 nm. The temperature and humidity dependence of conductivity of the sub-100 nm films is quite different from those of the thicker films. Furthermore, in the former thickness range, the value of conductivity markedly increases with reducing the film thickness, and its thickness dependence follows a power law with a fixed index of −2.1. This size-scaling effect can be explained by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…It is important to note that the amount of H atom in the film increases in accordance with the height of conductivity in the order of Hf5Si95, Hf3Si97 N Hf20Si80. We can conclude from the results of GDOES that amorphous M n Si 1 − n O x nanomembranes contain sufficient acidic sites throughout the membrane interior as in the case of aluminosilicate film [7,9].…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…It is important to note that the amount of H atom in the film increases in accordance with the height of conductivity in the order of Hf5Si95, Hf3Si97 N Hf20Si80. We can conclude from the results of GDOES that amorphous M n Si 1 − n O x nanomembranes contain sufficient acidic sites throughout the membrane interior as in the case of aluminosilicate film [7,9].…”
Section: Resultsmentioning
confidence: 86%
“…Thus, the ionic conduction in amorphous Hf n Si 1 − n O x films at elevated temperature is not attributed to the water-mediated proton transport which occurs in a xerogel compound [15,16]. These behaviors of Hf n Si 1 − n O x film is very similar to the proton conductivity of Al n Si 1 − n O x film which reveal the conduction of a native proton on Brønsted acid sites of aluminosilica framework [7][8][9]. The depth profile of H atom in the sample as-prepared at 450°C for 1 h in air was measured by glow discharge optical emission spectroscopy (GDOES) [10] (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…40 The result indicated that the aluminosilicate film was gastight even though the film was as thin as ∼100 nm. Therefore, this inorganic thin film is also promising as a corrosion-resistant coating.…”
mentioning
confidence: 99%